Konflik dan Aktualisasi Diri Tokoh Utama Pada Novel Pulang Karya Leila S. Chudori: Kajian Psikologi Humanistik Abraham Maslow - Jihad Akbar Ramadhan; Dardanila Dardanila; Nurhayati Harahap (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
The novel Pulang by Leila S. Chudori tells the story of people trapped in historical and political conflict as a result of the 1965 events in Indonesia, which had an impact on social life and caused deep psychological pressure on individuals. These conditions gave rise to various internal conflicts related to loss of identity, sense of security, and meaning of life. This study aims to describe the conflicts and self- actualization of the main character, Dimas Suryo, in the novel Pulang based on Abraham Maslow's humanistic psychology. A literary psychology approach is used to understand the character's psychological dynamics through the fulfillment of the hierarchy of human needs, which includes physiological needs, safety, love, self- esteem, and self-actualization. The research method used is descriptive qualitative with reading, literature study, and note-taking techniques. Data were obtained from the novel Pulang as the primary data source and books and scientific journals as secondary data sources. The results of the study show that Dimas Suryo experiences various conflicts, including political conflict, guilt conflict, ideological conflict, marital conflict, identity conflict, and illness conflict, which affect the fulfillment of his psychological needs and hinder the process of self-actualization. However, through self-reflection and a long struggle, the main character undergoes a transformation that leads to a more mature, humanistic, and meaningful understanding of life. Novel Pulang karya Leila S. Chudori mengisahkan pengalaman manusia yang terjebak dalam konflik sejarah dan politik akibat peristiwa 1965 di Indonesia yang berdampak pada kehidupan sosial dan menimbulkan tekanan psikologis mendalam bagi individu. Kondisi tersebut melahirkan berbagai konflik batin yang berkaitan dengan kehilangan identitas, rasa aman, dan makna hidup. Penelitian ini bertujuan untuk mendeskripsikan konflik dan aktualisasi diri tokoh utama, Dimas Suryo, dalam novel Pulang berdasarkan kajian psikologi humanistik Abraham Maslow. Pendekatan psikologi sastra digunakan untuk memahami dinamika kejiwaan tokoh melalui pemenuhan hierarki kebutuhan manusia yang meliputi kebutuhan fisiologis, rasa aman, kasih sayang, harga diri, hingga aktualisasi diri. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan teknik baca, studi pustaka, dan catat. Data diperoleh dari novel Pulang sebagai sumber data primer serta buku dan jurnal ilmiah sebagai sumber data sekunder. Hasil penelitian menunjukkan bahwa Dimas Suryo mengalami berbagai konflik, antara lain konflik politik, konflik rasa bersalah, konflik ideologi, konflik pernikahan, konflik identitas, dan konflik penyakit, yang memengaruhi pemenuhan kebutuhan psikologisnya dan menghambat proses aktualisasi diri. Namun, melalui refleksi diri dan perjuangan panjang, tokoh utama mengalami aktualisasi diri yang mengarah pada pemaknaan hidup yang lebih matang, humanis, dan bermakna.